Seismic Performance Analysis of Regular and Irregular Buildings Based on SNI 1726:2019 Standards (International Journal of Architecture and Urbanism, 2024)
This study analyzes the seismic performance of regular and irregular building structures according to the SNI 1726:2019 standards. Four building models were developed: one regular structure and three irregular structures, using data from the earthquake-prone Tarutung region in Sumatra. The analysis, conducted with ETABS software, focused on key seismic parameters including base shear, story shear, displacement, torsion, and column reinforcement. Results showed that regular buildings performed better under seismic loads, exhibiting lower base shear, story shear, and torsion due to their symmetrical configuration and uniform mass distribution. But the Country is such that where even less than irregular structures also faced more in seismic force and higher displacement at across the horizontal direction, torsional effects were seen much stronger especially with significant irregularities. This resulted in non-uniform distribution of forces and localized higher requirements for column reinforcement. These results underline how regular buildings, where developing countries have the most capacity to make improvements in construction quality and safety on a large scale, are actually quite resilient structures against seismic forces. This research demonstrates the significance of complying with seismic design codes and offers perspective which may assist engineers to develop irregular building structures that are more earthquake resistant.